Ganoderma Lucidum Leather as a Sustainable Alternative Potential for Fashion Industry - Cazan, Bogdan; Iordache, Ovidiu-George; Mihai, Carmen; Perdum, Elena; Dinca, Laurentiu (Technium Sustainability, 2024)
Leather demand in fashion industry has increased in the recent years, making it more difficult for the leather producers to provide the needed quantity. This matter led to an increase in the number of the livestock farms thus creating other environmental issues as water pollution, deforestation, overgrazing and gas emissions. Beside this, the processing of animal hides into leather requires extra steps that involves toxic chemicals which eventually will get released into the environment. In this regard, one of the solutions we aimed for was the production of fungi leather. Fungi leather requires less water and surface to grow, being obtained through the upcycling of agricultural and forestry waste and by-products, using fungal growth process. There is a wide range of filamentous fungi that can be used for this process, highest yield ones being wood-decaying fungi or white rot fungi from genres Polyporus sp., Ganoderma sp., Trametes sp., Pleurotus sp., Fomes sp.. This study focused mainly on the Ganoderma lucidum strain and on the production of pure mycelium mats. Pure mycelium mats obtained this way can adopt multiple properties and show promising as substitutes for present petrochemically produced materials or animal leather. The process we used is divided in chemical and physical treatment. The main methods used in chemical treatment were deacetylation of chitin and the cross-linking of chitosan. Following cross-linking the pure mycelium mat (PMM) was subjected to a plasticizer agent. In the end, after physical treatment a minimum viable product was obtained.